2003
DOI: 10.1105/tpc.012070
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of a Chromatin Boundary Appears to Shield a Transgene in Tobacco from RNA Silencing

Abstract: We present isogenic transgenic tobacco lines that carry at a given chromosomal position a ␤ -glucuronidase ( GUS ) reporter gene either with or without the presence of the matrix-associated region known as the chicken lysozyme A element. Plants were generated with the Cre-lox site-specific recombination system using heterospecific lox sites. Analysis of GUS gene expression in plant populations demonstrates that the presence of the A element can shield against RNA silencing of the GUS gene. Protection was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 77 publications
2
26
1
Order By: Relevance
“…However, we have observed that cells with the same genotype can include both GFP negative and GFP positive cells and that the Rb7 MAR reduces the frequency of GFP negative, nonexpressing cells. These results are consistent with previous suggestions (Allen et al, 2000;Mlynarova et al, 2003) that MARs can reduce the severity of gene silencing. A large portion of the MAR effect can now be understood as an effect on the frequency of silencing events within a clone of transgenic cells.…”
Section: Discussionsupporting
confidence: 83%
“…However, we have observed that cells with the same genotype can include both GFP negative and GFP positive cells and that the Rb7 MAR reduces the frequency of GFP negative, nonexpressing cells. These results are consistent with previous suggestions (Allen et al, 2000;Mlynarova et al, 2003) that MARs can reduce the severity of gene silencing. A large portion of the MAR effect can now be understood as an effect on the frequency of silencing events within a clone of transgenic cells.…”
Section: Discussionsupporting
confidence: 83%
“…This has not been found for weak S/MARs, though the possibility remains that weak S/MARs are involved in dynamic folding of loops into subdomains (Avramova et al, 1995). S/MARs have been further demonstrated in a variety of functional tests to act as insulators (Mlynarova et al, 2003), according to the loop domain model, by protecting a loop from the effects of the neighboring chromatin or associated enhancer sequences. However, this is not a general rule since other S/MARs do not show such insulating activity in enhancer-blocking assays, and some known insulators do not show properties typical for S/MARs (Jarman and Higgs, 1988;Kellum and Schedl, 1992;Li and Stamatoyannopoulos, 1994;Antes et al, 2001;Razin, 2001).…”
mentioning
confidence: 99%
“…Remnants of retroelements have been identifi ed in the vicinity of unstably expressed transgenes [18], and methylation of retroelements has been suggested to affect adjacent sequences, leading to transcriptional repression [25,26]. Conversely, matrix attachment regions (MARs), dispersed throughout eukaryotic genomes [27] have in some cases been shown to confer position-and copy-numberindependent control of transgene expression [28][29][30]. Furthermore, abrupt changes in GC content between genomic DNA and a transgenic insert have been suggested to make the transgene conspicuous to silencing mechanisms [31,32].…”
mentioning
confidence: 99%